Pengembangan Booklet Materi Daun (Folium) pada Mata Kuliah Morfologi Tumbuhan - Reny Dwi Riastuti; Hadiwinarto Hadiwinarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to test the feasibility of the Leaf material (folium) booklet in the Plant Morphology course and assess student responses to the Leaf (folium) material booklet in the Plant Morphology course. The method used is Research and Development (R&D) with a 4D (four-D) development model consisting of 4 stages, namely Define (defining), Design (planning), Develop (development) and Disseminate (deployment). The results showed that the validation value of material experts was 90%, linguists were 82.5% and media experts were 80%. The results of the student response questionnaire to the booklet got a score of 83.75%, with a very decent category. In conclusion, the booklet has been successfully developed and is feasible to use. Keywords: Booklet, Leaves, Plant Morphology